Assessing Nursing Students' Clinical Competencies Using a Problem-Focused Objective Structured Clinical Examination. (March 2017) - Zhu, Xuemei; Yang, Li; Lin, Ping; Lu, Guizhi; Xiao, Ningning; Yang, Shufen; Sui, Shujie
The objectives of this study were to develop, implement, and evaluate an innovative modified Objective Structured Clinical Examination (OSCE) model, and to compare students' performance of different clinical skills as assessed by standardized patients and OSCE examiners. Data were obtained from final year undergraduate students undergoing the modified OSCE as a graduation examination. Seventy-seven students rotated through four stations (nine substations). Standardized patients scored students higher than examiners in history taking (9.14 ± 0.92 vs. 8.42 ± 0.85), response to emergency event (8.88 ± 1.12 vs. 7.62 ± 1.54), executive medical orders (8.77 ± 0.96 vs. 8.25 ± 1.43), technical operation (18.21 ± 1.26 vs. 16.91 ± 1.35), nursing evaluation (4.53 ± 0.28 vs. 4.29 ± 0.52), and health education stations (13.79 ± 1.31 vs. 11.93 ± 2.25; p < .01). In addition, the results indicated that the difference between standardized patient and examiner scores for physical examination skills was nonsignificant (8.70 ± 1.18 vs. 8.80 ± 1.27; p > .05). The modified, problem-focused, and nursing process–driven OSCE model effectively assessed nursing students' clinical competencies, and clinical and critical thinking.